The Factors that are Related to Visiting Participants of the Chronic Disease Management Program to the Prolanis Aerobic Club in Lampung Central Regency, 2020 - Samsul Maarif; Bambang Setiaji; Noviansyah Noviansyah; Dian Utama Pratiwi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Over the past two decades, there has been a significant epidemiological transition, non-infectious diseases have become a major burden, even though the burden of non-infectious diseases is still heavy. The number of Prolanis Clubs in Central Lampung is 78, which consists of 39 clubs which are in 39 Community Health Centers and 39 Clubs from Private First Level Health Clinics and Private Practitioners. The number of Prolanis participants in Central Lampung Regency was 3397 participants, with the most in the ArafaH Clinic as many as 396 participants. The purpose of this study is to determine the factors associated with the visit of Chronic Disease Management Program participants to the Prolanis Club in Central Lampung Regency in 2020. This study uses a cross sectional study design. The study population was all Prolanis participants. A sample of 215 people. Data collection using a questionnaire filled directly by respondents, data analysis using logistic regression tests. The results showed there was a relationship of knowledge (p value 0.002. OR 2.5), attitude (p value 0,000. OR 5.29), perception (p value 0,000. OR 3.8), family support (p value 0.003. OR 2 , 4), accessibility (p value 0,000. OR 3,2) with Prolanis participants 'visit to Prolanis Club in Central Lampung Regency in 2020. Attitude is the most dominant factor related to Prolanis participants' visit to Prolanis Club, which has the highest OR value, namely 11,266. Suggestions for the research are expected that health workers carrying out prolanist activities increase their role as educators by providing education about Type 2 Diabetes Mellitus and Hypertension and emphasizing the importance of participating in prolanist activities so as to increase the positive attitude of prolanist participants towards Prolanist activities.